Amorphous Lithium Sulfide as Lithium‐Sulfur Battery Cathode with Low Activation Barrier. Issue 12 (25th March 2019) - Lodovico, Lucas; Milad Hosseini, Seyed; Varzi, Alberto; Passerini, Stefano
Abstract : Herein, the synthesis of a novel lithium sulfide (Li2 S)‐based material is presented. The material is composed of Li2 S and lithium sulfenamide, which are formed in and coprecipitated from an ethylenediamine solution as an amorphous, but solid compound. The sulfenamide compound is shown to be an effective carbon source to obtain carbon‐coated Li2 S via post‐processing. Both the pristine and carbon‐coated materials are characterized by a series of physicochemical methods and preliminarily investigated for application in batteries. The pristine material possesses a remarkably low activation potential. This ease of activation is particularly beneficial for solid‐state cells, where the material shows a much better performance than the commercially available Li2 S. Abstract : Embedding ethylenediamine molecules into Li2 S particles decreases their crystallinity, leading to smaller activation barriers. This is specifically beneficial to solid‐state cells, where the material is directly converted from Li2 S to sulfur. The result is solid‐state cells with high specific capacities and coulombic efficiency from the first cycle onward.